2019
DOI: 10.1136/ijgc-2018-000131
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in opioid use and postoperative pain scores after elective laparotomy with implementation of enhanced recovery after surgery protocol on a gynecologic oncology service

Abstract: ObjectiveEnhanced Recovery After Surgery (ERAS) protocols are designed to mitigate the physiologic stress response created by surgery, to decrease the time to resumption of daily activities, and to improve overall recovery. This study aims to investigate postoperative recovery outcomes following gynecologic surgery before and after implementation of an ERAS protocol.MethodsA retrospective chart review was performed of patients undergoing elective laparotomy at a major academic center following implementation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 34 publications
1
19
0
Order By: Relevance
“…The close and timely communication of the ERAS team helps to identify potential di culties and optimize ERAS procedures. Recent studies have shown that continual auditing of the protocol can help to improve compliance [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The close and timely communication of the ERAS team helps to identify potential di culties and optimize ERAS procedures. Recent studies have shown that continual auditing of the protocol can help to improve compliance [31].…”
Section: Discussionmentioning
confidence: 99%
“…It is necessary to weigh the side effects against the strong potency of opioids. Although some guidelines and reviews mentioned about multimodal analgesia in ERAS program, there are still some controversies, such as the application of patient-speci c multimodal analgesia programs for elderly patients and multimodal analgesic management for preoperative opioid users[10,28,31,32].…”
mentioning
confidence: 99%
“…Our granular opioid use data over the post-operative period are the first to show a sustained and significant reduction in opioid use by NSAIDs, while adjusting for significant confounders. Multimodal analgesia is a tenet of ERAS protocols and ERAS implementation has been found to decrease post-operative opioid consumption 27 28. Although greater compliance with ERAS elements is associated with improved patient outcomes,29 data on which individual elements are most crucial to patient benefit are currently limited.…”
Section: Discussionmentioning
confidence: 99%
“…One key element of the enhanced recovery pathway is to decrease opioid use through increased utilisation of multimodal pain control (Table 1). As a result of implementing enhanced recovery pathways with multimodal analgesia, multiple single‐centre studies have shown significant reductions of peri‐operative opioid requirements and lower reported pain scores in gynaecologic patients who underwent laparotomy when compared with historical controls who had the same procedure without a pathway in place [28–30]. Studies have also reported statistically significant reductions in 30‐day surgical site infection risk among patients undergoing these procedures and have reported success with specific interventions including: setting patient and caregiver expectations; early patient education; pre‐operative antimicrobial washing; and timely administration of prophylactic antibiotics before surgery [31–33].…”
Section: Reporting Outcome Benefits Of Enhanced Recoverymentioning
confidence: 99%